Prototype application of the prolanis service management information online system (SIMPELPRO) to support capitation indicators achievement based on service commitment in first-level of healthcare facilities at the Pratama Clinic, Poltekkes, Ministry of Health, Semarang - Setya Wijayanta; Rizal Ginanjar; Isnaini Qoriatul Fadhillah (Poltekkes Kemenkes Semarang, 2023)
Non-communicable diseases (PTM) are catastrophic diseases with the highest causes of death in Indonesia and are still a health problem and a threat to economic growth in Indonesia. The government has established the Social Security Administrative Body (BPJS) for Health through Law Number 24 of 2011 as a form of constitutional commitment to managing the implementation of public health insurance through the National Health Insurance. The lack of information and outreach regarding the Chronic Disease Management Program (Prolanis) in FKTP has resulted in the target of fulfilling the Prolanis Controlled Participant Ratio indicator not being achieved. The RPPB indicator at the Primary Clinic of the Semarang Ministry of Health Poltekkes in 2019 is still 10%. So to overcome this it is necessary to do a number of things, namely by providing information, outreach, and education regarding the types of Prolanis activities and their benefits and objectives. The better the level of information the participants have, the greater the tendency to use Prolanis. The purpose of this study was to develop a Prolanis Service Management Information System Application Prototype (SIMPELPRO) to Support the Achievement of Service Commitment-Based Capitation Indicators at Primary Health Facilities, the Primary Clinic, Poltekkes, Ministry of Health, Semarang. The research method used in this study uses descriptive research methods, with primary data sources, namely using interviews and observations of officers and doctors at the clinic, as well as secondary data from documentation and literature. For system design in this study, researchers will use the prototype method for system development including the stages of needs analysis, implementation, and testing. The results of this study resulted in a system that facilitates officers in terms of data management, data search and presentation of PROLANIS educational materials for participants who have registered as PROLANIS participants at the Primary Clinic of the Health Polytechnic of the Ministry of Health Semarang.